2020
DOI: 10.3390/molecules25143175
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen Fertigation and Harvesting Time on Plant Growth and Chemical Composition of Centaurea raphanina subsp. mixta (DC.) Runemark

Abstract: The aim of the present study was to evaluate the effect of nitrogen fertigation (0, 200, 400, and 600 ppm of total nitrogen) and harvesting time (9 March 2018 and 19 April 2018) on the plant growth, chemical composition, and bioactive properties of Centaurea raphanina subsp. mixta plants. The highest yield of fresh leaves was observed for the treatment of 200 ppm of N without compromising nutritional value. The increasing nitrogen levels resulted in an increase of α- and total tocopherols and sugars content, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
17
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 76 publications
10
17
2
Order By: Relevance
“…A list with the names and the types of cultivars is presented in Table 6. After emergence, young seedlings were thinned to three plants per container with equal distances, using 15 containers for each cultivar [49]. Cultivation was initially performed in an unheated glasshouse at the experimental farm of the University of Thessaly in Velestino, Greece, while the containers were moved outdoors in March 2019, given the rising temperatures within the greenhouse.…”
Section: Growing Conditionsmentioning
confidence: 99%
“…A list with the names and the types of cultivars is presented in Table 6. After emergence, young seedlings were thinned to three plants per container with equal distances, using 15 containers for each cultivar [49]. Cultivation was initially performed in an unheated glasshouse at the experimental farm of the University of Thessaly in Velestino, Greece, while the containers were moved outdoors in March 2019, given the rising temperatures within the greenhouse.…”
Section: Growing Conditionsmentioning
confidence: 99%
“…For Centaurea raphanina , four studies compared the plant grown in situ, or wild, with the ex situ, or cultivated [ 17 ], through a further analysis of the soil enrichment effects on the plant antimicrobial properties [ 16 , 20 , 37 ]. The wild C. raphanina displayed the highest capacity to inhibit bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in many studies MWEPs and antibiotics are used at the very same concentration (mg/mL) to compare their antimicrobial activities. In several cases, MWEPs extracts do work like conventional antibiotics (e.g., ampicillin), if not at lower concentrations [8,12,16,17,21,26,30,[36][37][38][39]44], especially for bacterial species known for displaying ABR. In future studies, it will be advisable to analyze the effectiveness of the extracts formulated with different nanocarriers.…”
Section: How Much Of Mweps Extracts Are Necessary Vs Antibiotics?mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid fraction in MAPs is generally low and data on the composition of fatty acids is essential, especially with respect to the content of polyunsaturated fatty acids (PUFA) and saturated fatty acids (SFA) [ 34 ]. The fatty acid composition of the mixtures under study is shown in Table 5 .…”
Section: Resultsmentioning
confidence: 99%